Corner restrictions and their application to bending plate analyses by the boundary element method. (October 2018) - Paiva, João Batista
Abstract: In this paper, a study of the boundary restrictions at corner plates is presented for analysis by the boundary element method. From a hypothesis regarding the uniqueness of the stress tensor and algebraic manipulation, the equivalent shear force and bending moment were shown to be null for some types of corners. With the imposition of these boundary conditions, the results obtained using the boundary element method are highly consistent with those obtained by the finite element method with very refined meshes. Ways to write additional equations for each corner of the plate when the traction and its respective displacement are zero are also presented to avoid singularity in the system of equations.